Empowerment of Animalia Classification Material: A Review of Literature - Puti, Tunjung Nala; Karyanto, Puguh; Fatmawati, Umi (Universitas Muhammadiyah Surakarta, 2023)
This article is a literature review that discusses the characteristics of animal classification as biology learning material. Animalia classification material is one of the materials that are difficult for students to understand. So the purpose of this literature review is to analyze the characteristics of Animalia classification material to determine and find the right way of empowerment so that students can receive the material well. The method used is a systematic literature review (SLR) with PRISMA guideline, reviewed from 2013-2023 with certain criteria. The literature obtained based on these criteria obtained as many as 150 articles from Google Schoolar, Scopus, and Web of Science, but after analysis based on abstracts, keywords, research methods, and discussion, 21 articles were finally selected. The results of the literature review show that Animalia classification material can be empowered with a learning model that is collaborative learning combined with online visual media. One of the learning innovations that can be used is project-based learning in online media.